2018
DOI: 10.3390/w10101354
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall-Induced Landslide Susceptibility Using a Rainfall–Runoff Model and Logistic Regression

Abstract: Conventional landslide susceptibility analysis adopted rainfall depth or maximum rainfall intensity as the hydrological factor. However, using these factors cannot delineate temporal variations of landslide in a rainfall event. In the hydrological cycle, runoff quantity reflects rainfall characteristics and surface feature variations. In this study, a rainfall–runoff model was adopted to simulate the runoff produced by rainfall in various periods of a typhoon event. To simplify the number of factors in landsli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…On the basis of the concept of the effective stress, the shear strength of the soil can be written using the extended Mohr-Coulomb failure criterion [8] as: (12) where τ denotes the shear strength of the soil; c is the effective cohesion; φ represents the angle of effective friction; σ is the total normal stress; u a and u w are the pore air pressure and pore water pressure, respectively; u a − u w denotes the matric suction; and χ denotes the effective stress parameter dependent on the degree of saturation. Much experimental evidence has shown that the effective stress parameter χ of unsaturated soil is a highly nonlinear function of the matric suction.…”
Section: Soil Failure Modulementioning
confidence: 99%
See 3 more Smart Citations
“…On the basis of the concept of the effective stress, the shear strength of the soil can be written using the extended Mohr-Coulomb failure criterion [8] as: (12) where τ denotes the shear strength of the soil; c is the effective cohesion; φ represents the angle of effective friction; σ is the total normal stress; u a and u w are the pore air pressure and pore water pressure, respectively; u a − u w denotes the matric suction; and χ denotes the effective stress parameter dependent on the degree of saturation. Much experimental evidence has shown that the effective stress parameter χ of unsaturated soil is a highly nonlinear function of the matric suction.…”
Section: Soil Failure Modulementioning
confidence: 99%
“…where S is the saturation degree, S r denotes the residual degree of saturation, and S e represents the effective saturation. From Equation (12) and the water retention curve (i.e., Equation (2)), a highly nonlinear relationship between the effective stress parameter and the matric suction can be observed for unsaturated soil. Equations (12) and (14) show that the unsaturated shear strength is related to the saturation degree.…”
Section: Soil Failure Modulementioning
confidence: 99%
See 2 more Smart Citations
“…Logistic regression analysis, also called binary regression analysis, is a widely used statistical model when the dependent variable is binary, e.g., landslide occurrence or nonoccurrence, and independent variables are in the numerical type (e.g., slope), in the categorical type (e.g., lithology), or in both types (e.g., [44]). As it is beyond the present paper's scope, some detailed verification of applying the logistic regression model to landslide prediction can be referred to in the literature (e.g., [45][46][47]).…”
Section: Landslide Modelmentioning
confidence: 99%